In-vitro Study of Cytotoxicity and Apoptosis Effects of Clinacanthus nutans (Burm.f.) Lindau Extracts on Colorectal Cancer Cell Lines, HT-29 and HCT-116 - Joyce Hui Yie, Phung; Weng Kit, Ban; Isabel Lim, Fong; Khong, Heng Yen (Joyce Phung Hui Yie, 2023)
Cancer is one of the leading causes of mortality in Malaysia, with colorectal cancer as the most common cancer in males and the second most common cancer in females. Colorectal cancer causes high mortality as it is hardly detected during the early stage yet has a 15-year window of intervention. Hence, the discovery of the chemoprevention method is important to delay carcinogenesis and prevent the recurrence of cancer. Clinacanthus nutans (Burm.f.) Lindau (C. nutans), from Acanthaceae family, is known as Sabah Snake Grass or ‘Belalai Gajah’ in Malaysia. It is popular in Southeast Asia for its medicinal properties such as anticancer, anti-inflammation and antiviral properties. Therefore, this study aimed to determine the total phenolic content (TPC), total flavonoid content (TFC), antioxidant activity, and anticancer properties of C. nutans leaves extracts on human colorectal cancer cell lines, HCT-116 and HT-29 in dose- and time-dependent manners. The ground C. nutans leaves were extracted with methanol, chloroform, and acetone for 30 minutes and 24 hours, respectively. The TPC and TFC were determined spectrophotometrically using the Folin-Ciocalteu and aluminium chloride colourimetric methods. 1,1-Diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging assay was used to determine the antioxidant activity. The antiproliferation and apoptotic capabilities were studied using MTT and apoptosis (Annexin V-FITC and PI staining method) assays, respectively. C. nutans methanol extracts and 24 hours of extraction time resulted in higher extraction yield (7.65g ± 0.13) than its counterparts. Acetone extracted C. nutans at 30 minutes and 24 hours resulted in the highest TPC values of 3.06 mg GAE/g and 3.18 mg GAE/g, respectively. On the other hand, methanol extracted C. nutans at 30 minutes and 24 hours exhibited the highest TFC (0.49 mg QE/g and 0.50 mg QE/g, respectively) and strongest antioxidant activity (IC50 values at 24.25 μg/mL and 19.67 μg/mL; AAEAC at 22.14% and 27.31%, respectively) than chloroform and acetone extracts. The methanol extracts were selected for in vitro study. HCT-116 cells revealed higher antiproliferative effects than HT-29 cells using methanol extracted C. nutans at 30 minutes when treated for 24 hours and 72 hours. On the contrary, HCT-116 cells exhibited lower antiproliferative effects when treated for 48 hours. Methanol extracted C. nutans at 24 hours exhibited stronger antiproliferation activity when treated on HT-29 cells with less cytotoxicity to normal cells for 24, 48, and 72 hours. In addition, a low dose of 250 μg/mL methanol extracted C. nutans with 24 hours extraction time induced early and late apoptosis in HCT-116 and HT-29 cells after treatment for 72 hours. The methanol extract increased the late apoptosis of HCT-116 cells from 18.88% to 35.66% when treatment from 24 hours to 72 hours, respectively. The late apoptotic rate of HT-29 cells was increased from 14.28% to 20.67% when treatment was prolonged from 24 hours to 72 hours, respectively. In conclusion, methanol extracted C. nutans that underwent 24 hours extraction contained high TFC, exhibited high antioxidant activity, and able to inhibit the early and late stages of colorectal cancer cell growth by triggering apoptosis in dose- and time-dependent manners. The findings suggested that C. nutans possessed anticancer properties against colorectal cancer cell lines, HCT-116 and HT-29 through the apoptosis pathway. The findings provided new perspective for the future study to prove C. nutans as an alternative treatment against early and late stages colorectal cancer.